2008
DOI: 10.1016/j.eclnm.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum) and ginger (Zingiber officinale) attenuate structural nephropathy progression in streptozotocin-induced diabetic rats

Abstract: Introduction; Diabetic nephropathy is a consequence of the detrimental effects of biochemical abnormalities spearheaded by hyperglycemia. The consensus is that euglycemia is central in restraining diabetic nephropathy. Objective; This study investigated the hypoglycemic effect of garlic and ginger on the nephropathological structural occurrences in streptozotocin (STZ)‐induced diabetic rats. Method; Diabetic Sprague‐Dawley rats (serum glucose = SG > 350 mg/dl one week post‐STZ) received a daily dose (i.p. 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 33 publications
3
57
0
2
Order By: Relevance
“…Several phytochemical constituents including flavonoids, alkaloids, glycosides, saponins, tannins, and others obtained from various plant sources have been reported to be potent hypoglycemic agents (Al-Quattan et al, 2008). From the phytochemical analysis of G. longipetala, it was found to contain most of these constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Several phytochemical constituents including flavonoids, alkaloids, glycosides, saponins, tannins, and others obtained from various plant sources have been reported to be potent hypoglycemic agents (Al-Quattan et al, 2008). From the phytochemical analysis of G. longipetala, it was found to contain most of these constituents.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of 80% ethanol extract of garlic at dose of 0.5 g/kg decreased serum glucose, total cholesterol, and triglyceride in streptozotocin (STZ)-induced diabetic rats (8). Injection of garlic extract attenuated hypoglycemia and structural nephropathy progression in STZ-induced diabetic rats (9). It was reported that consumption of diet containing 5% garlic powder showed hypolipidemic effect in rats (13).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from several investigations has shown that garlic has antibacterial (5,6), anticarcinogenic (7), antidiabetic (8,9), antioxidant (10), and hypolipidemic effects (11,12). The administration of 80% ethanol extract of garlic at dose of 0.5 g/kg decreased serum glucose, total cholesterol, and triglyceride in streptozotocin (STZ)-induced diabetic rats (8).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that glomerular hypertrophy inhibited through consumption of herbal antioxidants extract such as garlic, ginger (22) and ginkgo biloba (23) in diabetic animals. In addition, glomerular hypertrophy inhibited by antioxidants such as Vit E and alpha tochopherol in diabetic rats (24)(25).…”
Section: Results From Antioxidant Therapy In Experimental Diabetic Nementioning
confidence: 99%